Persuasion in crowdfunding: An elaboration likelihood model of crowdfunding performance - Allison, Thomas H.; Davis, Blakley C.; Webb, Justin W.; Short, Jeremy C. (Journal of Business Venturing, 2017)
This study draws upon the elaboration likelihood model of persuasion (ELM) to develop and test a model of persuasive influence in crowdfunding. To test our hypothesized relationships, we drew upon a sample of 383 ventures taken directly from Kickstarter, coupled with a decision experiment conducted in a simulated crowdfunding context. Results suggest that issue-relevant information, such as entrepreneurs' education, matters most when funders possess greater ability and motivation to make careful evaluations. In contrast, cues, such as adopting a group identity, have their strongest influence among inexperienced, first-time funders, and when requested funding amounts are smaller.